HEMATOLOGICAL TOXICITIES OF CYCLIN-DEPENDENT KINASE 4 AND 6 INHIBITORS IN METASTATIC BREAST CANCER, SINGLE INSTITUTION EXPERIENCE - Kutić, Slobodan; Milović-Kovačević, Marijana; Novaković, Teodora; Ćosović, Vojislav; Purić, Mila (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Hematologic toxicity is the most common side effect of CDK4/6 inhibitors (CDK4/6i). Due to the novelty of these drugs, additional data are needed to identify potential predisposing factors for the development of hematologic toxicities.Aim: This study aims to investigate potential predisposing factors for the development of hematological toxicity during the administration of CDK 4/6i in the treatment of metastatic breast cancer.Methods: This retrospective descriptive study investigated the application of CDK4/6i in patients with metastatic breast cancer treated at the Breast Department of IORS from 1.1.2021 to 1.6.2024.Results: 128 patients were included in the study; 43% were treated with palbociclib and 57% with ribociclib. The median age was 60 years. Median follow-up was 12 months (range 2-23). Neutropenia was observed in 82.1% of patients and grade 3/4 in 43%. Dose reduction due to repeated grade 3/4 neutropenia was required in 21.1% of subjects. Grade 3/4 anemia and thrombocytopenia were observed in 0.8% and 1.6% of patients. Discontinuation of therapy due to hematological toxicities was necessary in 1.5% of patients. There was no statistically significant difference between the two drugs regarding the incidence of hematological toxicity (p=0.443). Previous use of chemotherapy in the metastatic phase of the disease was not significantly associated with the frequency of hematological toxicity (p=0.565). Palliative radiotherapy of bone lesions showed a statistically significant association with the need to reduce the dose of CDK4/6i (p=0.001, r=0.283). Median progression-free survival (PFS) was not reached, but there was no trend to suggest that CDK4/6i dose reduction affected PFS (p=0.719).Conclusion: Palliative radiotherapy of bone lesions is associated with more frequent dose reduction of CDK4/6i, but dose reduction of these drugs did not affect the length of survival.
Keywords: metastatic breast cancer; CDK4/6 inhibitors; hematological toxicity